The Expanding Workweek? Understanding Trends in Long Work Hours among U.S. Men, 1979–2006 - Kuhn, Peter; Lozano, Fernando (Journal of Labor Economics, 2008)
According to U.S. Census and Current Population Survey (CPS) data, employed U.S. men are more likely to work more than 48 hours per week today than 25 years ago. Using 1979–2006 CPS data, we show that this increase was greatest in the 1980s, among highly educated, highly paid, and older men, and among workers paid on a salaried basis. We examine some possible explanations for these changes, including composition effects. Among salaried men, increases in long work hours were greatest in detailed occupations and industries with larger increases in residual wage inequality and slowly growing real compensation at “standard” (40) hours.